Stimulasi Minat Belajar Agama Islam Menggunakan Strategi Cerita Pada Siswa SMP IT Al-Asror Sekampung Lampung Timur - Ikhwanul Amri; Akla Akla; Muhammad Ali (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2020)
This study aimed to analyze student’s learning interests and the learning process of Islamic education by using story strategies. This research was experimental research that was applying to learn using story strategies to the experimental group for several meetings. The sample in this study was 30 students of class VIII at SMP IT Al-Asror Sekampung. The research sample was classified into two groups; the experimental and the control group. The experimental group was a group of students taught by story strategies. The control group was a group of students taught by conventional strategies. The results showed that the use of story strategies in the learning process of Islamic education has been able to overcome student learning problems. The story strategy has been able to arouse enthusiasm and student attention. Curiosity to the storyline encourages students to always pay attention and concentrate on the story being heard. The results of statistical tests on the questionnaire data indicate there was an influence significant use of story strategies on student learning interests. High learning interest would have an impact on the achievement of learning objectives.